2019
DOI: 10.1136/bmjopen-2018-028507
|View full text |Cite
|
Sign up to set email alerts
|

Is inspiratory muscle training (IMT) an acceptable treatment option for people with chronic obstructive pulmonary disease (COPD) who have declined pulmonary rehabilitation (PR) and can IMT enhance PR uptake? A single-group prepost feasibility study in a home-based setting

Abstract: ObjectivesThis feasibility study aimed to assess the acceptability of inspiratory muscle training (IMT) in people with chronic obstructive pulmonary disease (COPD) who declined pulmonary rehabilitation (PR) as a potential treatment option or precursor to PR. Objectives were to assess attitudes to IMT, PR and alternatives to PR; factors influencing adherence with IMT and acceptability of outcome measures, research tools and study protocol.DesignA pragmatic, mixed methods, prepost feasibility study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Internal data storage allows for objective recording of intervention adherence and progression ( e.g. , changes in training load or achieved inspiratory volumes during training sessions) (95,96). Although these recordings overcome certain research limitations associated with self-reported information, objective documentation of training data does not help with IMST translation and implementation per se .…”
Section: Translational Potential Of High-resistance Imstmentioning
confidence: 99%
See 4 more Smart Citations
“…Internal data storage allows for objective recording of intervention adherence and progression ( e.g. , changes in training load or achieved inspiratory volumes during training sessions) (95,96). Although these recordings overcome certain research limitations associated with self-reported information, objective documentation of training data does not help with IMST translation and implementation per se .…”
Section: Translational Potential Of High-resistance Imstmentioning
confidence: 99%
“…Importantly, small feasibility trials for home-based, moderate-resistance IMST were performed in clinical populations (96,98), and provided initial insight on the ability of individuals to perform an IMST intervention without researcher oversight. In one study, adults with stable COPD performed 8 wk of moderate-resistance IMST (60% PI MAX , 30 breaths twice per day, 5 d·wk −1 ), with one session supervised in person.…”
Section: Translational Potential Of High-resistance Imstmentioning
confidence: 99%
See 3 more Smart Citations